Web-Based Parenting Skills Program for Pediatric Traumatic Brain Injury Reduces Psychological Distress Among Lower-Income Parents. Issue 5 (September 2015) - Raj, Stacey P.; Antonini, Tanya N.; Oberjohn, Karen S.; Cassedy, Amy; Makoroff, Kathi L.; Wade, Shari L.; Caplan, Bruce; Bogner, Jennifer; Brenner, Lisa
<x xml:space="preserve">Abstract</x> Objective: To examine changes in parent depression, psychological distress, parenting stress, and self-efficacy among participants in a randomized trial of a Web-based parent training program for pediatric traumatic brain injury (TBI). Methods: Primary caregivers of 37 children aged 3 to 9 years who sustained a moderate/complicated mild to severe TBI were randomly assigned to the intervention or control group, and both groups were equipped with home Internet access. The online parent training program was designed to increase positive parenting skills and improve caregiver stress management. It consisted of 10 core sessions and up to 4 supplemental sessions. Each session included self-guided Web content, followed by a videoconference call with a therapist to discuss content and practice parenting skills with live feedback. Families in the control group received links to TBI Web resources. Results: Parent income moderated treatment effects on parent functioning. Specifically, lower-income parents in the parenting skills group reported significant reductions in psychological distress compared with lower-income parents in the control group. No differences were found among higher-income parents for depression, parenting stress, or caregiver efficacy. Conclusions: Parent training interventions post-TBI may be particularly valuable for lower-income parents who are vulnerable to both environmental and injury-related stresses.